Biossolubilização do fonolito por bactérias diazotróficas e potencial de utilização em Brachiaria Brizantha VC. Marandu - MIRANDA, C. C. B. (2016)
Potassium (K) is one of the most required nutrients on crops and their availability to plants depends on soil reserves and potassium fertilization. Brazil imports about 90% of K used in agriculture, requiring, therefore, studies related to the discovery of alternative sources of this nutrient, such as use of phonolite rock dust. However, this has slow release of K in the soil, making the utilization unfeasible in agriculture. In this sense, the objectives of this study were to evaluate the potential solubilization of potassium phonolite rock by strains of associative diazotrophs supplied with two carbon sources and verify the feasibility of the use of the phonolite rock powder Brachiaria brizantha cv. Marandu and if the inoculation with bacterial strains diazotrophic and potassium solubilizing contribute to the development of forage. For this, two experiments were conducted, the first one in vitro, in which different bacterial strains were inoculated in Aleksandrov culture modified containing phonolite rock dust. We used two carbon sources, sucrose and glucose to check the effect of these on K. solubilization. The experiment was installed in design completely randomized in a factorial scheme 13 x 2, being 12 bacterial strains and an uninoculated control and two carbon sources. In general, all strains contributed to increase the concentration of K in the culture, highlighting the UNIFENAS 100-13 and 100-94 UNIFENAS strains, which were selected for use in the second experiment, in which these strains were inoculated in Brachiaria brizantha fertilized with different doses of phonolite. This experiment was installed in pots with capacity of 15 soil dm3, using the randomized complete block design (RBD), with treatments arranged in a factorial scheme 6 x 3 x 3, with utilization of KCl and five doses of phonolite: 100, 75, 50 and 25% of the recommended dose of KCl and 3 inoculants variables (UNIFENAS 100-13 strain, UNIFENAS 100-94 strain and control without inoculation), being evaluated by 3 cutting periods. Were evaluated morphological parameters and bromatologics. The use of rock silicate powder phonolite associated with diazotrophs in the development of B. brizantha cv. Marandu promoted better nutritional value as a substitute for potassium chloride ( KCl) . The UNIFENAS 100-94 inculante with the treatment without inoculation had better nutritional value.